Finding the sweet spot of memory modification: An fMRI study on episodic prediction error strength and type - Nina Liedtke; Marius Boeltzig; Falko Mecklenbrauck; Sophie Siestrup; Ricarda I. Schubotz (NeuroImage)
Previous research has highlighted the critical role of prediction errors (PEs) in signaling the need to adapt memory representations in response to unexpected changes in the environment. Yet, the influence of PE type and strength on memory remains underexplored. In this study, participants encoded naturalistic dialogues prior to undergoing fMRI scanning. During the fMRI session, they listened to dialogues that had been modified in their surface or gist, to varying extents. As expected, our findings revealed robust activation in the inferior frontal gyrus for all PEs. Notably, gist modifications elicited additional activations within the episodic memory network, including the hippocampus. A post-fMRI recognition test demonstrated that surface modifications had no significant impact on memory. Conversely, weak gist changes impaired memory for the original content and hindered learning of the modification. These weak gist changes also triggered activation in the parahippocampal cortex. These results underscore the importance of both the type and strength of PEs in shaping brain activations and memory outcomes, highlighting their complex interplay in cognitive processes.